2015
DOI: 10.1089/sur.2014.085
|View full text |Cite
|
Sign up to set email alerts
|

Infected Prostheses after Lower-Extremity Bone Tumor Resection: Clinical Outcomes of 100 Patients

Abstract: Megaprosthesis reconstructions may be infected in 8.6% of cases. Infections more commonly occur late, caused usually by S. epidermidis. The survival rate is higher with cementless megaprosthesis reconstructions and no different with respect to the type of tumor or megaprosthesis or the adjuvant treatments. One-stage revision is effective for acute post-operative infections; however, two-stage revision surgery is necessary for early and late infections. The rate of amputation because of occurrence or persistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 37 publications
3
56
2
2
Order By: Relevance
“…In our series, estimated infection‐rate (6% and 10% at 5 and 10 years, respectively) was lower than that reported in most of the previous studies, which reported infection rates up to 18% for all sites NIEPR . However, only 12.5% of DF NIEPR developed a deep infection in the series of Gilg et al These data emphasize the reduced risk of infection after DF NIEPR when compared to other sites …”
Section: Discussioncontrasting
confidence: 68%
“…In our series, estimated infection‐rate (6% and 10% at 5 and 10 years, respectively) was lower than that reported in most of the previous studies, which reported infection rates up to 18% for all sites NIEPR . However, only 12.5% of DF NIEPR developed a deep infection in the series of Gilg et al These data emphasize the reduced risk of infection after DF NIEPR when compared to other sites …”
Section: Discussioncontrasting
confidence: 68%
“…Marvogenis et al, showed similar survival rates of 88% at 10 years after two stage revisions. 11 Angelini, showed knee arthrodesis to be a viable salvage procedure for infected tumour prosthesis. However the success rates for the arthrodesis was only 50% at 5 years.…”
Section: %mentioning
confidence: 99%
“…13 The bacteriological profile in other series is similar to our series with the most common organisms seen being Staphylococcus spp. 5,11,[15][16][17] The sub species varied between studies with certain studies reporting Staph. epidermidis being more common than Staph.…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, endoprosthetic replacement surgery using tumor prostheses are today offered to 90% to 95% of all patients suffering from primary malignant bone tumors without compromising the oncological outcome . Amputation can, however, be a salvage procedure in case of a local recurrence of BS or implant failure …”
Section: Introductionmentioning
confidence: 99%